Navegation system for tubular upper digestive tract (2013)
The present endoscopy is an uncomfortable experience because these instruments are great size and magnitude, generating feelings of discomfort to the patient during the operation. It’s designed a device to scale, allowing counteract this effect improving the mechanism of endoscopy, being this a more effective and flexible, compared with capsule endoscopy and endoscopy equipment present because will include a biopsy system for analyzing gastroenterological diseases or gastric cancers, with bluetooth communication for visualization of real-time space tract.